Choice : challenges and perspectives for the European welfare states - Greve, Bent. (Chichester ; Malden, MA : Wiley-Blackwell, 2010)
"This book analyzes the impact of choice on welfare states in Europe. The recent focus on choice in many welfare states has created a more market-orientated approach, changed users to consumers, and increased the emphasis on private providers. By using a variety of methodologies and examples from different European countries and different sectors of the welfare state, the book examines the impact of these recent reforms on equality, not only from an economic perspective, but also in relation to gender and access to services. Theoretically and empirically informed, this book asks whether the shift towards more choice will ultimately benefit the users and providers of the welfare state, and have a positive impact on society as a whole"--
Can choice in welfare states be equitable? / Bent Greve -- The other Le Grand? Evaluating the 'other invisible hand' in welfare services in England / Ian Greener and Martin Powell -- Exit, voice and quality in the English education sector / Deborah Wilson -- When 'choice' and 'choice' are not the same : institutional frameworks of choice in the German welfare system / Florian Blank -- Choosing welfare or losing social citizenship? Citizens' free choice in recent Italian welfare state reforms / Paolo R. Graziano -- The 'consumer principle' in the care of elderly people : free choice and actual choice in the German welfare state / Melanie Eichler and Birgit Pfau-Effinger -- A comparative discussion of the gendered implications of cash-for-care schemes : markets, independence and social citizenship in crisis? / Kirstein Rummery -- Challenging solidarity? An analysis of exit options in social policiese / Menno Fenger -- Freedom of choice through the promotion of gender equality / Steven Saxonberg.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Social choice -- Europe; Welfare state -- Europe; Consumers' preferences -- Europe; Choix collectif -- Europe; z; Consommateurs -- z; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Human Services; Consumers' preferences; Social choice; Welfare state; Europe